The wholeness of early Chinese texts: Mu Shi 牧誓, Huainanzi 淮南子, and Wu Cheng 武成 - Smith, CJ (2020)
What does it mean for a text to be a whole? How do texts achieve wholeness? And how can one determine when they do so? Questions of wholeness have been at the heart of Chinese text studies since the Western Han 漢 (205 BC–9 AD), when scholars attempted some of the earliest known reconstructions, and constructions, of pre-imperial texts. In the two millennia since, almost all early Chinese texts studied have been evaluated in terms of their wholeness, yet within this scholarship, there are many ideas about what makes these texts whole. In many cases, “wholeness” refers to the extent to which a text is seen to resemble an earlier, if not an imagined original form. Alternatively, “wholeness” is taken to refer to a function of texts’ intrinsic features, such as their content or structure. This project, by contrast, posits that “wholeness” does not refer to an immutable property of texts themselves, but to a contingent hermeneutical device or function within the open, kaleidoscopic process of reading, itself negotiated and re-negotiated through this very process. Reading, in short, does not reveal text wholeness (or lack thereof), but rather allows for texts to be made whole, in different and plural ways.